Hello from MrBillDoesMath!
Answer:
6x
Discussion:
7x = 7 times x
x = 1 times x
So both terms are "like" terms in x:
7x - x = (7-1)x = 6x
Thank you,
MrB
Answer:
105 minutes.
Step-by-step explanation:
first you would subtract 60 by 20 to get 40 then your time would be at 9:00 so in order to get to 10:00 you would have 60 minutes which you would add the 40 to to get 100 minutes then add 5 to bring your time to 10:05 and your total number of minutes to 105
Answer:
Option B.
Step-by-step explanation:
The given expression is
![5p+3p+(-9)](https://tex.z-dn.net/?f=5p%2B3p%2B%28-9%29)
We need to find an expression which is equivalent to the given expression.
Combine like terms.
![(5p+3p)-9](https://tex.z-dn.net/?f=%285p%2B3p%29-9)
![8p-9](https://tex.z-dn.net/?f=8p-9)
The simplified form of given expression is 8p-9. So, option A is incorrect.
In option B, the given expression
![3(p+(-3))+5p](https://tex.z-dn.net/?f=3%28p%2B%28-3%29%29%2B5p)
![3(p-3)+5p](https://tex.z-dn.net/?f=3%28p-3%29%2B5p)
Using distributive property, we get
![3p-9+5p](https://tex.z-dn.net/?f=3p-9%2B5p)
Combined liker terms.
![(5p+3p)-9](https://tex.z-dn.net/?f=%285p%2B3p%29-9)
![8p-9](https://tex.z-dn.net/?f=8p-9)
It is same as the simplified form of given expression.
Therefore, the expression 3(p+(-3))+5p is equivalent to the given expression and correct option is B.
Answer:
The minutes wouldn't it be hours?
Step-by-step explanation:
Step-by-step explanation:
Let
where
![f(x) = x^4](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%5E4)
![g(x)= (1 -2x^5)^6](https://tex.z-dn.net/?f=g%28x%29%3D%20%281%20-2x%5E5%29%5E6)
![h(x)= (5 - 8x^3)^2](https://tex.z-dn.net/?f=h%28x%29%3D%20%285%20-%208x%5E3%29%5E2)
so that
![y(x) = x^4(1 -2x^5)^6(5 - 8x^3)^2](https://tex.z-dn.net/?f=y%28x%29%20%3D%20x%5E4%281%20-2x%5E5%29%5E6%285%20-%208x%5E3%29%5E2)
Recall that the derivative of the product of functions is
![y'(x)=f'(x)g(x)h(x)+f(x)g'(x)h(x)+f(x)g(x)h'(x)](https://tex.z-dn.net/?f=y%27%28x%29%3Df%27%28x%29g%28x%29h%28x%29%2Bf%28x%29g%27%28x%29h%28x%29%2Bf%28x%29g%28x%29h%27%28x%29)
so taking the derivatives of the individual functions, we get
![f'(x) = 4x^3](https://tex.z-dn.net/?f=f%27%28x%29%20%3D%204x%5E3)
![g'(x) = 6(1 - 2x^5)^5(-10x^4)](https://tex.z-dn.net/?f=g%27%28x%29%20%3D%206%281%20-%202x%5E5%29%5E5%28-10x%5E4%29)
![h'(x) = 2(5 - 8x^3)(-24x^2)](https://tex.z-dn.net/?f=h%27%28x%29%20%3D%202%285%20-%208x%5E3%29%28-24x%5E2%29)
So the derivative of y(x) is given by
![y'(x) = 4x^3(1 -2x^5)^6(5 - 8x^3)^2 + x^4 6(1 -2x^5)^5(-10x^4)(5 - 8x^3)^2 + x^4(1 -2x^5)^6 2(5 - 8x^3)(-24x^2)](https://tex.z-dn.net/?f=y%27%28x%29%20%3D%204x%5E3%281%20-2x%5E5%29%5E6%285%20-%208x%5E3%29%5E2%20%2B%20%20x%5E4%206%281%20-2x%5E5%29%5E5%28-10x%5E4%29%285%20-%208x%5E3%29%5E2%20%2B%20%20x%5E4%281%20-2x%5E5%29%5E6%202%285%20-%208x%5E3%29%28-24x%5E2%29)
or
![y'(x) = 4x^3(1 -2x^5)^6(5 - 8x^3)^2](https://tex.z-dn.net/?f=y%27%28x%29%20%3D%204x%5E3%281%20-2x%5E5%29%5E6%285%20-%208x%5E3%29%5E2)
![\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:- 60x^8(1 -2x^5)^5(5 - 8x^3)^2](https://tex.z-dn.net/?f=%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A-%2060x%5E8%281%20-2x%5E5%29%5E5%285%20-%208x%5E3%29%5E2)
![\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:- 48x^6(1 -2x^5)^6 2(5 - 8x^3)](https://tex.z-dn.net/?f=%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A%5C%3A-%2048x%5E6%281%20-2x%5E5%29%5E6%202%285%20-%208x%5E3%29)